The regulator’s dilemma in proving algorithmic cartels against the principle of fair competition in the digital economy era - Tengku Andrias Prayudha; David Banjarnahor; Auliya Rochman; Sy. Muhammad Ikhsan; Alifah Nur Fitriana Naridha (Privietlab, 2025)
The rapid development of the digital economy, marked by the adoption of pricing algorithms, has introduced new dynamics to Indonesia's competition law landscape. Algorithmic systems enable autonomous price setting based on market data learning without direct human intervention. This condition potentially gives rise to algorithmic cartels, a form of market coordination occurring without explicit agreement, yet producing anti-competitive effects similar to conventional cartels. The national legal framework, specifically Law No. 5 of 1999 and KPPU Regulation No. 4 of 2010, remains inadequate to address this phenomenon, as it is still anchored to a traditional paradigm requiring the element of “agreement” as a prerequisite for proving violation. This study aims to analyze the dilemma faced by the regulator (KPPU) in proving the existence of algorithmic cartels against the principle of fair competition in the digital era. Employing a normative juridical approach, this study examines relevant legislation, academic literature, and international policies from the OECD and European Commission. The findings indicate a regulatory gap in Indonesia's competition law regarding proof involving autonomous systems. Furthermore, the KPPU faces conceptual and technical obstacles in determining legal intent (legal intent) and the validity of digital evidence derived from algorithmic systems. The study concludes that proving algorithmic cartels must shift from an intent-based approach to an effects-based approach, which focuses on assessing the economic impact on market structure and consumer welfare. Therefore, strategic recommendations include reinterpreting the element of “agreement” in Article 1, paragraph 7, and Article 11 of Law No. 5 of 1999 to encompass algorithmic coordination that generates anti-competitive effects. Additionally, the KPPU is mandated to develop digital evidence guidelines and strengthen the multidisciplinary institutional capacity to effectively oversee algorithmic behavior. These steps are crucial for Indonesian competition law to adapt to the realities of the digital economy while ensuring justice and legal certainty.